β-delayed multiple-particle emitters minibeam radiation therapy: first dosimetric evaluation with Monte Carlo simulations - Corvino, Angela; Schneider, Tim; Prezado, Yolanda (Frontiers in Physics, 2024)
Radiation therapy, one of the most effective methods for cancer treatment, is still limited by the tolerances of normal tissues surrounding the tumor. Innovative techniques like spatially fractionated radiation therapy (SFRT) have been shown to increase normal tissue dose resistance. Heavy ions also offer high-dose conformity and increased relative biological effectiveness (RBE) when compared to protons and X-rays. The alliance of heavy ions and spatial fractionation of the dose has the potential to further increase the therapeutic index for difficult-to-treat cases today. In particular, the use of β-delayed multiple-particle emitters might further improve treatment response, as it holds the potential to increase high linear energy transfer (LET) decay products in the valleys of SFRT (low-dose regions) at the end of the range. To verify this hypothesis, this study compares β-delayed multiple-particle emitters (⁸Li, ⁹C, ³¹Ar) with their respective stable isotopes (⁷Li, ¹²C, ⁴⁰Ar) to determine possible benefits of β-delayed multiple-particle emitters minibeam radiation therapy (β-MBRT). Monte Carlo simulations were performed using the GATE toolkit to assess the dose distributions of each ion. RBE-weighted dose distributions were calculated and used for the aforementioned comparison. No significant differences were found among carbon isotopes. In contrast, ⁸Li and ³¹A exhibited improved RBE-weighted dose distributions with an approximately 12-20% increase in the Bragg-peak-to-entrance dose ratio (BEDR) for both peaks and valleys, which favors tissue sparing. Additionally, ⁸Li and ³¹A exhibited a lower peak-to-valley dose ratio (PVDR) in normal tissues and higher PVDR in the tumor than ⁷Li and ⁴⁰Ar. Biological experiments are needed to conclude whether the differences observed make β-delayed multiple-particle emitters advantageous for MBRT.